Feasibility of paying people who use drugs cash to distribute naloxone within their networks - Nikki M. Lewis; Rebecca P. Smeltzer; Trevor J. Baker; Andrea C. Sahovey; Justine Baez; Erika Hensel; Brandon Poole; Cecelia Stewart; Allyson G. Cogan; Mackenzie Bullard; Jessica L. Taylor (Harm Reduction Journal, 2024)
Abstract Introduction Immediate access to naloxone is needed to prevent fatal opioid-related overdoses in the presence of fentanyl analogs saturating the opioid supply. Peer models engage impacted populations who are not accessing naloxone through standard venues, yet compensating peers who utilize syringe service programs with cash stipends to distribute naloxone within networks of people who use drugs is not well described. Methods As part of the HEALing Communities Study, syringe service program-based interventions were developed in Holyoke and Gloucester, MA, which paid people who use drugs (“peers”) cash to distribute naloxone. Early program outcomes were evaluated for the time each program was funded within the HCS study period. Results During 22 study-months of observation, peers in two communities distributed 1104 naloxone kits. The total cost of peer compensation for program delivery was $10,510. The rate of peer-distributed naloxone per 100 K population reached 109 kits/mo and 222 kits/mo in the two communities. Participating peers addressed gaps in harm reduction outreach and distributed naloxone and other harm reduction equipment to individuals who were not syringe service program participants, expanding organizational reach. Being compensated with unrestricted cash stipends supported dignity and acknowledged peers’ work in overdose prevention. Conclusion The underutilization of compensated peer models is often attributed to funding and organizational barriers. These programs demonstrate that providing cash stipends to peers is feasible and expanded naloxone distribution at two existing syringe service programs. Providing cash stipends for peers who engage in secondary naloxone distribution offers promise in delivering naloxone to people not accessing syringe services.